1981
DOI: 10.1083/jcb.89.3.510
|View full text |Cite
|
Sign up to set email alerts
|

Fluidity properties and liquid composition of erythrocyte membranes in Chediak-Higashi syndrome.

Abstract: We have earlier shown through electron spin resonance (ESR) studies of leukocytes that membranes of cells from both Chediak-Higashi syndrome (CHS) mice and humans have abnormally high fluidity . We have extended our studies to erythrocytes . Erythrocytes were labeled with the nitroxide-substituted analogue of stearic acid, 2-(3-carboxypropyl)-4,4-dimethyl-2-tridecyl-3-oxazolidinyloxyl, and ESR spectra were obtained . Order parameter, S, at 23°C, was 0.661 and 0.653 for erythrocytes of normal and CHS mice (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Many studies have demonstrated that modification of the polyunsaturated fatty acid composition of mammalian membranes alters their fluidity and function (Stubbs and Smith, 1984;Zamaria, 2004). Interestingly, the membranes of erythrocytes from both mice and humans with ChediakHigashi Syndrome (CHS) are abnormally fluid (Haak et al, 1979;Ingraham et al, 1981). The proportions of PCs(18:2) in these membranes are also elevated to levels comparable with those seen when iPLA 2 is inhibited.…”
Section: Journal Of Cell Science 120 (23)mentioning
confidence: 76%
“…Many studies have demonstrated that modification of the polyunsaturated fatty acid composition of mammalian membranes alters their fluidity and function (Stubbs and Smith, 1984;Zamaria, 2004). Interestingly, the membranes of erythrocytes from both mice and humans with ChediakHigashi Syndrome (CHS) are abnormally fluid (Haak et al, 1979;Ingraham et al, 1981). The proportions of PCs(18:2) in these membranes are also elevated to levels comparable with those seen when iPLA 2 is inhibited.…”
Section: Journal Of Cell Science 120 (23)mentioning
confidence: 76%
“…Increasing membrane fluidity results from increasing the freedom of molecular motion and has been observed in several situations where lipid composition has been altered: 1)decreasing the cholesterol content relative to the amount of phospholipid; 2) increasing the phospholipid content relative to the amount of protein; 3) increasing the phosphotidylcholine content relative to sphingomyelin; 4) increasing the phosphatidylethanolamine content relative to phosphatidylcholine; 5) increasing the degree of unsaturation of fatty acids; and 6) decreasing the fatty acid chain length (22). From our data, it appears that the reduction in membrane fluidity of cord cells is due primarily to diminished phospholipid/protein ratios, which are also associated with increased cholesterol/phospholipid molar ratios relative to those of adult cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to provide some additional basis for interpretation of the data in Figs. 10 and 11, we created liposomes containing lipids representative of the outer or inner leaflets of the erythrocyte membrane (34,35) and repeated the measurements with DPH and laurdan at both high and low cholesterol concentrations. As shown in Fig.…”
Section: Erythrocytes Depleted Of Cholesterolmentioning
confidence: 99%